Heterogeneity of Executive Function Abilities in Recently Detoxified Patients with Alcohol Use Disorder: Evidence from a Cluster Analysis. (25th December 2020) - Schmid, Franca; Benzerouk, Farid; Barrière, Sarah; Henry, Audrey; Limosin, Frédéric; Kaladjian, Arthur; Gierski, Fabien
Abstract : Background: Impairments of executive functions (EF) have been consistently reported in patients with alcohol use disorder (AUD), mostly in studies which were based on comparisons of means between groups. However, given the high heterogeneity in AUD patients, this approach could actually cover a wide range of EF patterns. In the present study, we addressed the paucity of the literature about cognitive heterogeneity in AUD by applying a cluster analytical approach on EF measures. Methods: Seventy‐eight withdrawn AUD patients and 77 healthy Control participants completed measures targeting a variety of EF components. We then used cluster analysis to identify subgroups of AUD patients. Furthermore, the AUD subgroups were compared to the Control group to establish their specific EF patterns. Results: Findings showed that AUD patients could be divided into 3 clusters based on their EF performances. A first cluster accounting for half of the AUD sample was characterized by unimpaired EF (Cluster 1). The 2 other clusters displayed major EF deficits but differed regarding the deficient EF component. While Cluster 2 was mainly impaired on measures of rule deduction and mental flexibility, Cluster 3 was mainly characterized by a lower processing speed and impaired inhibition of an ongoing motor response. Differences in EF performances of AUD patients could be related to differences in premorbid cognitive reserve, impulsiveness patterns, and withdrawal complications. Conclusions: This study highlights the importance of the cognitive heterogeneity in AUD by showing that AUD patients display substantially different EF patterns. Future studies should try to go beyond mere group comparisons to further deepen our understanding about cognitive differences between AUD patients. In the long run, this could lead to more personalized prevention and treatment programs specifically tailored to the patient's impairments. Abstract : Executive function patterns of alcohol use disorder (AUD) patients as revealed by cluster analysis based on the number of categories completed on the Wisconsin Card Sorting Test (WCST categories), the flexibility index of the Trail Making Test (TMTB‐A), the average reaction time on the Go/No‐go task (Go/No‐go RT) and the average reaction time on the Stop Signal task (Stop Signal RT) and data of control participants' performances on the same measures.